2016
DOI: 10.1055/s-0036-1585457
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Women with Polycystic Ovary Syndrome after a Program of Resistance Exercise Training

Abstract: Purpose Aerobic exercises may improve quality of life (QoL) in women with polycystic ovary syndrome (PCOS). However, there is no data on the effect of resistance exercise training (RET) programs on the QoL of women with PCOS. Thus, this study aimed to assess the effect of a 16-week RET program on QoL in PCOS women. Methods This 16-week case-control study enrolled 43 women with PCOS (PCOS group, PCOSG) and 51 healthy pre-menopausal controls aged 18 to 37 years (control group, CG). All women underwent a supervis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 51 publications
0
34
0
2
Order By: Relevance
“…Isolated pharmacological treatment has been found to be ineffective in controlling the clinical condition of PCOS, and complementary measures such as lifestyle changes and exercise are recommended (Costa et al, 2018; Kogure et al, 2016; Lara et al, 2015; Lopes et al, 2018; Ribeiro et al, 2016; Thomson et al, 2010). Previous studies conducted by our research group have demonstrated the positive effects of physical strength training on QoL (Ramos et al, 2016), while in another study, the benefits of aerobic exercise in PCOS were demonstrated (Costa et al, 2018). Relatedly, the positive effects of exercise on QoL have been demonstrated in different clinical conditions and different populations (Brown et al, 2018; Hayashino et al, 2018; Vasiliadis and Bélanger, 2018).…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Isolated pharmacological treatment has been found to be ineffective in controlling the clinical condition of PCOS, and complementary measures such as lifestyle changes and exercise are recommended (Costa et al, 2018; Kogure et al, 2016; Lara et al, 2015; Lopes et al, 2018; Ribeiro et al, 2016; Thomson et al, 2010). Previous studies conducted by our research group have demonstrated the positive effects of physical strength training on QoL (Ramos et al, 2016), while in another study, the benefits of aerobic exercise in PCOS were demonstrated (Costa et al, 2018). Relatedly, the positive effects of exercise on QoL have been demonstrated in different clinical conditions and different populations (Brown et al, 2018; Hayashino et al, 2018; Vasiliadis and Bélanger, 2018).…”
Section: Introductionmentioning
confidence: 69%
“…Different protocols have been used to prove the beneficial effects of exercise on QoL in other populations such as older persons and individuals with cancer and type II diabetes (Brown et al, 2018; Hayashino et al, 2018; Vasiliadis and Bélanger, 2018). In studying women with PCOS, the most recent protocols have involved physical strength training and aerobic exercise (Costa et al, 2018; Ramos et al, 2016). A study by Ramos et al (2016) included a protocol of progressive intensity with a frequency of three times per week, over a 16-week period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanistic impacts of exercise and physical activity on cardiometabolic and reproductive features of PCOS are well described 52,68–70 . Whilst acknowledging the limitations in QOE (sample size, study type, heterogeneity of interventions), improved glycaemic and reproductive outcomes, QoL and functional capacities have been shown 52,54,55,66,68–71 . Limited community‐based/epidemiological studies show positive associations between self‐reported physical activity and mental health status, 58,59 and between vigorous exercise and better health outcomes in PCOS 72 .…”
Section: Resultsmentioning
confidence: 99%
“…21 There were also improvements in quality of life and sexual function as complementary benefits. 22,23 Evidence in the literature suggests that a PRT protocol associated with the practice of calisthenics (exercises that use the body's own weight as the primary tool) promoted significant changes in body composition, even with the increase of total weight and lean muscle strength in overweight and obese individuals. It also promoted improvements in several health-related domains, such as anxiety, depression, and quality of life.…”
mentioning
confidence: 99%